2017
DOI: 10.5152/eej.2017.16032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Calcium Hydroxide Intracanal Dressing on Dentinal Tubule Penetration of Two Root Canal Sealers

Abstract: Objective: The aim of this study was to evaluate the effect of a calcium hydroxide (CH) dressing on the tubular penetration of two endodontic sealers, AH Plus (Dentsply Maillefer, Ballaigues, Switzerland) and MTA Fillapex (Angelus, Londrina, Brazil). Methods: Seventy-two mandibular premolars with a single root canal were prepared with ProFile.04 rotary instruments (Dentsply Maillefer) and divided into four groups. In two groups, an intracanal CH dressing was placed for 15 days. The obturations were performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
1
1
1
Order By: Relevance
“…While the root-third had no significant effect on the sealer penetration, the penetration depth in all the groups was higher in the coronal-third than in the middle and apical third. The finding that sealer penetration depth was higher in the coronal than in the middle and apical region is in accordance with previous studies ( 17 , 25 ). Er,Cr:YSGG laser activation resulted in significantly higher sealer penetration depth than sonic agitation and syringe irrigation, immaterial of the root third and the medicament used.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the root-third had no significant effect on the sealer penetration, the penetration depth in all the groups was higher in the coronal-third than in the middle and apical third. The finding that sealer penetration depth was higher in the coronal than in the middle and apical region is in accordance with previous studies ( 17 , 25 ). Er,Cr:YSGG laser activation resulted in significantly higher sealer penetration depth than sonic agitation and syringe irrigation, immaterial of the root third and the medicament used.…”
Section: Discussionsupporting
confidence: 93%
“…The exact thickness of each slice was measured using a digital caliper to 0.04 mm accuracy (Mitutoyo, Tokyo, Japan). Specimens were visualized under confocal laser scanning microscope to measure sealer penetration depth into the dentinal tubules ( 17 ). representative images from each group at coronal and apical thirds are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Muchos factores podrían tener un efecto en la penetración de los materiales en los túbulos dentinarios, como la capa de frotis 29 , las However, the results of the current investigation differs from that published by Cruz et al 2017 26 , in which, they conducted a study with the purpose of evaluating the effect of calcium hydroxide (HC), on the tubular penetration of two endodontic sealants, Ah Plus and MTA Fillapex, identifying that the use of Intracanal CH did not interfere with sealant penetration in the apical third of the canal; however, the penetration of Ah Plus in the middle third decreased.These results can be caused by different parameters such as the root canal anatomy, the size and density of the dentinal tubules, the difficulty in completing the elimination of the intracanal HC medication and the dentinal slit 21,22 . Bernardes et al 2010 27 , reported that with or without the presence of HC residues, sealability penetrability tends to increase in the aponal-coronal direction; These results are consistent with those of the current investigation.…”
Section: Odontología Odontologíacontrasting
confidence: 83%
“…No obstante, los resultados de la actual investigación difiere de lo publicado por Cruz et al 2017 26 , en el cual, realizaron un estudio con la finalidad de evaluar el efecto del hidróxido de calcio (HC), en la penetración tubular de dos selladores de endodoncia, Ah Plus y MTA Fillapex, identificando que el uso del CH intracanal no interfirió con la penetración del sellador en el tercio apical del conducto; sin embargo, disminuyó la penetración de Ah Plus en el tercio medio. Estos resultados pueden ser causados por diferentes parámetros como, la anatomía del canal radicular, el tamaño y densidad de los túbulos dentinarios, la dificultad para completar la eliminación de la medicación intracanal de HC como del barrillo dentinario 21,22 .…”
Section: Odontología Odontologíaunclassified
“…which showed that the penetrability of BioRoot RCS was higher up as compared with epoxy resin-based sealer. [ 29 30 ] According to Pawar et al ., leakage was exhibited due to insufficient adhesion between gutta-percha and the sealer. Owing to the resin it contains and its quicker setting time, AH Plus has a propensity to shrink and induce early debonding from the root canal.…”
Section: Discussionmentioning
confidence: 99%